Market Expansion to Myanmar: Entry Strategy Formulation for PT Telekomunikasi Indonesia (The Indonesian Journal of Business Administration, 2013)
Globalization in the telecommunications industry has been growing rapidly and drastically overcome geographical barriers between the domestic and international markets. Telecommunications company needs to survive and achieve growth encourages them to compete not only in the domestic market but also in overseas markets. To enter foreign markets, companies must choose the most suitable strategy which influenced by the condition of the company, the company's home country conditions, the following conditions of the destination country industry. PT.Telkom Indonesia itself has begun to enter foreign markets since 2006. In recent years, along with the shift towards openness in Myanmar in the political and economic systems, PT.Telkom Indonesia is planning to expand the market to Myanmar. This final project will focus on assessing Myanmar country and telecommunication industry attractiveness, suitability of Myanmar to theÂ  objective ofÂ  PT.Telkom and formulate appropriate entry mode to enter Myanmar for PT.TelkomÂ  target market expansion. The assessment process will use several theoretical framework, Porter Diamond framework to analyze advantage of doing business in Myanmar, Porter's Five Forces framework to analyze the competitiveness of the telecommunications industry and Franklin.R.Root models to formulate an appropriate entry mode. This theoretical framework will guide the collection and analysis of empirical data. The method of research using qualitative methods. Primary data collect using the instrument via an email interview with management of PT. Telkom. Secondary data using material fromÂ  group discussion forum with Indonesian Ambassador to Myanmar, published articles in the internet, company annual reports, government report, books, and other related research. Based on the results of the qualitative analysis, authors concluded that Myanmar as a country and the telecommunications industry is favourable and attractive market. Appropriate mode to entering the market for PT. Telkom Indonesia is a sequential approach the first step is to open a branch office as â€œlistening portâ€ and then move towards capital investments either on its own or jointly with local companies (regulation consideration). To penetrate Myanmar market, author recommends PT.Telkom to offer cellular product with broadband capability in a selected area. As a controlling mechanism, PT.Telkom shall combine parenting system as a combination of planning control and financial controlÂ Keywords: International Business, Target Country Attractiveness, Telecommunication Industry Attractiveness, Objective of PT.Telkom, Preferable Entry Strategy